Praktik Perlombaan Kicauan Burung - Masliani Pangaribuan; Muhammad Arsad Nasution (Jurnal El-Thawalib, 2022)
The practice of singing bird competitions is often carried out in Ujungpadang Village, South Padangsidimpuan District, Padangsidimpuan City, namely on Sundays once a week and once a month.Each participant buys a registration ticket to take part in the competition.Ticket prices vary depending on the class and the event that will be followed by the participants of the competition.The awarding of prizes is determined by the number of participants who take part in the competition, and the proceeds from ticket sales. The objectives to be achieved in this study were to find out the practice of the chirping of birds that occurred in Ujungpadang Village, South Padangsidimpuan District, Padangsidimpuan City and an overview of Muamalah Fiqh on the practice of the competition. This research is a qualitative field research, namely data collection is carried out by direct observation to Ujungpadang Village, South Padangsidimpuan District, Padangsidimpuan City, documentation, and interviews with the Chair of the Organization/Committee, Contest Participants, Judges, and the community who know about the practice of the chirping birds competition. occurred in the Village. The results of this study indicate that the implementation of the practice of chirping birds competition in Ujungpadang Village, South Padangsidimpuan District, Padangsidimpuan City, namely each participant is required to buy a registration ticket to the committee to take part in the competition. The factors that cause people to be interested in participating in the competition include as a means of entertainment, to channel the hobbies of bird lovers, the selling price of birds becomes more expensive and they are interested in the prizes for the competition. The practice of the chirping of birds that occurred in Ujungpadang Village, South Padangsidimpuan District, Padangsidimpuan City, can be said to be a competition that is not appropriate and is not allowed. This is because the prize giving to the winner has an element of maysir, with the funds given coming from the money for the registration ticket for the competition participants.